1983
DOI: 10.1159/000123460
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Changes in Plasma, Pituitary and Hypothalamic Immunoreactive β-Endorphin: Effects of Diurnal Variation, Adrenalectomy, Corticosteroids, and Opiate Agonists and Antagonists

Abstract: Immunoreactive β-endorphin (ir-βEP) levels were determined in plasma, anterior pituitary (AP), neuro-intermediate lobe (N-IL) and hypothalamus (HT) of intact rats and adrenalectomized rats subjected to swimming stress. In intact rats, plasma ir-βEP was elevated fourfold, and ir-βEP levels in AP and N-IL significantly reduced after 30 min swimming; in contrast, HT ir-βEP in these animals was not affected. In adrenalectomized animals, similar but even more marked changes were found in plasma and tissue ir-βEP fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…However, the levels of P-endorphin IR and y-endorphin IR were not affected by adrenalectomy. In another study also no change was observed in hypothalamic p-endorphin IR content after 6 days of adrenalectomy [26].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, the levels of P-endorphin IR and y-endorphin IR were not affected by adrenalectomy. In another study also no change was observed in hypothalamic p-endorphin IR content after 6 days of adrenalectomy [26].…”
Section: Discussionmentioning
confidence: 86%
“…This finding suggests that glucocorticoids act on enzymes capable of y-endorphin for mation, in addition to the well-documented action on POMC gene transcription. POMC messenger RNA pool, biosynthesis of POMC peptides, and the release of POMC peptides from the anterior pituitary gland [18,19,26,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these considerations the au thors would then favor the hypothesis that, during pregnancy, the concentration of hypothalamic p-opioid receptors becomes more elevated because of the stressful conditions represented by pregnancy itself and by the oncoming delivery. Brain opioid peptides have been actually demonstrated to be significantly affected by stressful stimuli of various nature [27],…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that these two chronic stressors, which are known to activate different central pathways and differently stimulate POMC-related peptides in anterior and intermediate lobes [20][21][22], have similar effects in reducing hypothalamic [1-EP content and abolishing its responsiveness to an acute challenge. The different central pathway activation linked to swimm ing or to ether stress is confirmed by the observation that GnRH contents are increased by the former model of stress, but not by the latter.…”
Section: Discussionmentioning
confidence: 81%